Calcium-Prolactin Secretion Coupling in Rat Pituitary Lactotrophs Is Controlled by PI4-Kinase Alpha - Kučka, Marek; Gonzalez-Iglesias, Arturo E.; Tomić, Melanija; Prévide, Rafael M.; Smiljanic, Kosara; Sokanovic, Srdjan J.; Fletcher, Patrick A.; Sherman, Arthur; Balla, Tamas; Stojilkovic, Stanko S. (Frontiers in Endocrinology, 2021)
The role of calcium, but not of other intracellular signaling molecules, in the release of pituitary hormones by exocytosis is well established. Here, we analyzed the contribution of phosphatidylinositol kinases (PIKs) to calcium-driven prolactin (PRL) release in pituitary lactotrophs: PI4Ks - which control PI4P production, PIP5Ks - which synthesize PI(4,5)P2 by phosphorylating the D-5 position of the inositol ring of PI4P, and PI3KCs – which phosphorylate PI(4,5)P2 to generate PI(3,4,5)P3. We used common and PIK-specific inhibitors to evaluate the strength of calcium-secretion coupling in rat lactotrophs. Gene expression was analyzed by single-cell RNA sequencing and qRT-PCR analysis; intracellular and released hormones were assessed by radioimmunoassay and ELISA; and single-cell calcium signaling was recorded by Fura 2 imaging. Single-cell RNA sequencing revealed the expression of Pi4ka, Pi4kb, Pi4k2a, Pi4k2b, Pip5k1a, Pip5k1c, and Pik3ca, as well as Pikfyve and Pip4k2c, in lactotrophs. Wortmannin, a PI3K and PI4K inhibitor, but not LY294002, a PI3K inhibitor, blocked spontaneous action potential driven PRL release with a half-time of 20 min when applied in 10 µM concentration, leading to accumulation of intracellular PRL content. Wortmannin also inhibited increase in PRL release by high potassium, the calcium channel agonist Bay K8644, and calcium mobilizing thyrotropin-releasing hormone without affecting accompanying calcium signaling. GSK-A1, a specific inhibitor of PI4KA, also inhibited calcium-driven PRL secretion without affecting calcium signaling and Prl expression. In contrast, PIK93, a specific inhibitor of PI4KB, and ISA2011B and UNC3230, specific inhibitors of PIP5K1A and PIP5K1C, respectively, did not affect PRL release. These experiments revealed a key role of PI4KA in calcium-secretion coupling in pituitary lactotrophs downstream of voltage-gated and PI(4,5)P2-dependent calcium signaling.